Peran Guru dalam Pelaksanaan Pembelajaran Jarak Jauh di Tengah Wabah Covid - 19 - Siti Sabaniah; Dadan F Ramdhan; Siti Khozanatu Rohmah (Edunesia: Jurnal Ilmiah Pendidikan, 2021)
Abstract, Distance Learning should be well prepared from planning, implementing, to evaluating learning. This encourages research to examine how the role of teachers in the learning process is seen from the learning process. The focus of this research is to describe the Role of Teachers in the Implementation of Distance Learning, from the planning, implementation, and evaluation of learning. This research uses a descriptive qualitative research model. This research was conducted at MI Mathlau'ul Huda with the subject of the research being the teachers, in this case the teachers were given questionnaires and interviews to find out some indicators of the teacher's role, (1) the teacher's role as a source of learning in distance learning the teacher provided the source of learning among them namely the theme books and programs that the government made through television namely on TVRI; (2) the teacher's role as a demonstrator in this distance learning where the teacher provides facilities such as media for example with video media to help students in the learning process; (3) the teacher's role as a motivator gives the teacher motivating students. The motivation provided by the teacher also varies, there are those who provide motivation with rewards and also those that go directly to students (4) the role of the teacher as a manager in distance learning here the teacher acts as a manager of learning so that learning can be directed according to the basic competencies and learning objectives that must be achieved; (5) the teacher's role as an evaluator here the teacher's role is to provide an evaluation in order to know the extent to which students master a learning material. Abstrak, Pembelajaran Jarak Jauh seyogianya harus dipersiapkan dengan baik dari mulai perencanaan, pelaksanaan, sampai kepada evaluasi pembelajaran. Hal ini mendorong penelitian untuk mengkaji bagaimana peran guru dalam proses pembelajaran yang dilakukan dilihat dari proses pembelajaranya. Fokus penelitian ini adalah untuk mendeskripsikan peran guru dalam pelaksanaan pembelajaran jarak jauh, dari mulai perencanaan, pelaksanaan, dan evaluasi pembelajaran. Penelitian ini menggunakan model penelitian deskriptif kualitatif. Penelitian ini dilakukan di MI Mathlau’ul Huda dengan subjek penelitianya adalah para guru, dalam hal ini para guru diberikan angket dan wawancara untuk mengetahui beberapa indikator dari peran guru, (1) peran guru sebagai sumber belajar, dalam pembelajaran jarak jauh guru memberikan sumber belajar, yaitu buku tema dan program yang pemerintah buat melalui televisi yaitu di TVRI; (2) peran guru sebagai demonstrator, pada pembelajaran jarak jauh ini dimana guru memberikan fasilitas seperti, media contohnya dengan media video untuk membantu siswa dalam proses pembelajaran; (3) peran guru sebagai motivator, guru memberikan memotivasi kepada peserta didik. Motivasi yang diberikan guru juga beragam ada yang memberikan motivasi dengan reward dan juga ada yang melalui langsung kepada peserta didik (4) peran guru sebagai pengelola, dalam pembelajaran jarak jauh disini guru berperan sebagai pengelola pembelajaran, agar pembelajaran dapat terarah sesuai dengan kompetensi dasar dan tujuan pembelajaran yang harus dicapai; (5) peran guru sebagai evaluator disini guru berperan untuk memberikan evaluasi agar mengetahui sejauh mana peserta didik menguasai suatu materi pembelajaran. Terakhir mengenai faktor pendukung dan penghambat peran guru dalam pelaksanan pembelajaran jarak jauh.